2009
DOI: 10.1016/j.rehab.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty in a spinal cord-injured patient: A case report

Abstract: Patients with spinal cord injuries are prone to knee hydrarthrosis (also known as "water on the knee"), which can cause pain, functional impairment and the restriction of social activities. Total knee arthroplasty is a potentially appropriate treatment. Here, we report on a patient presenting partial T12 AIS grade C paraplegia who was able to walk with two forearm crutches, an ankle-foot orthosis on the right leg and a knee-ankle-foot orthosis on the left leg. Thirteen years after the spinal cord injury, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Periprosthetic infection risk had been reported to be higher in the SCITKA patients because of the higher prevalence of UTI in these patients. 9 , 12 , 14 , 24 , 26 Our study showed that the risk of periprosthetic joint infection was almost 4 times higher in the SCITKA patients, but it failed to show statistical significance. It is not uncommon for PP to have pressure ulcers that fail to heal after several years of treatment.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Periprosthetic infection risk had been reported to be higher in the SCITKA patients because of the higher prevalence of UTI in these patients. 9 , 12 , 14 , 24 , 26 Our study showed that the risk of periprosthetic joint infection was almost 4 times higher in the SCITKA patients, but it failed to show statistical significance. It is not uncommon for PP to have pressure ulcers that fail to heal after several years of treatment.…”
Section: Discussionmentioning
confidence: 63%
“…There are only two case reports on patients with paraplegia undergoing TKA: the age of the patient in the study by Koubaa et al was 42 years and the age of the patient in the study by Zietek et al was 47 years. 24,25 By contrast, the mean age of our patient population is older than the case reports and may be related to the large sample size.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation